Preparation of Porous Materials by Magnesium Phosphate Cement with High Permeability - Lai Zhenyu; Hu Yang; Fu Xiaojie; Lu Zhongyuan; Lv Shuzhen (Advances in Materials Science and Engineering)
High permeability and strength magnesium phosphate cement (MPC) with porosity, average pore size, and compressive strength varied from 63.2% to 74%, 138.7 μm to 284.7 μm and 2.3 MPa to 4.7 MPa, respectively, were successfully prepared by combining the physical foaming method and chemically entrained gas method at room temperature. The effects of borax content, chemical foaming agent content, zinc powder content and W/S ratio on the porosity, pore size distribution, compressive strength, and permeability of the MPC were investigated. The results indicate that the chemical foaming agent content tends to have little impact on the porosity and compressive strength, and the zinc powder content has the most significant influence on the average pore size of MPC. The air pores distribution and connectivity of MPC were mainly controlled by the borax content, W/S ratio, and chemical foaming agent content. Zinc powder played a destructive role in the pores formed by the early physical foaming and led to an increase in pore size and a large number of through pores, which increased the permeability of the materials.